(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the problem of psychological overcoming of difficult life situations. The main scientific approaches of coping-behavior category in Ukraine and foreign psychology are presented. The psychological model of the structural-dynamic organization of the coping-process is outlined. The article is an attempt to detact effective ways of solving difficult life situation. The results of an empirical study of dominant coping-strategies among young people are presented.